Idly passing the time this morning I thought of a – b = a + (-b).

Fair enough, it is the interpretation of subtraction in the extended positive/negative number system.

I then thought of a – (b + c)

Sticking to the rules I got a + (-(b + c))

To proceed further I had to **guess** that -(b + c) = (-b) + (-c)

and then, quite ok, a – (b + c) = a – b – c

But -(b + c) = (-b) + (-c) is guesswork.

I cannot see a rule to apply to this situation.

The only way forward is to use -1 as a multiplier:

So a – b = a + (-1)b = a + (-b),

and then -(b + c) = (-1)(b + c) = (-1)b + (-1)c = (-b) + (-c)

by the distributive law.

It’s not surprising that kids have trouble with negative numbers!

Do we just assert that the distributive law applies everywhere, even when it is only defined with ++’s ?